Optimalisasi Pemanfaatan Daun Kelor Sebagai Produk Olahan Bernilai Gizi dan Bernilai Ekonomi Tinggi - Astrid Maharani; Retno Murwanti (Journal of Community Development, 2021)
Moringa oleifera is the one of familiar plants in Harjomulyo Village. The one factor of the number moringa plants in Harjomulyo Village because it’s too easy to grow in tropical climates, have high rainfall and are resistant to dry seasons. The problem of Harjomulyo Village is a lack of knowledge related to nutritional value and high economic value related to moringa plants which are widely available in Harjomulyo Village. The aim of this service is to educate the Moringa plant into processed nutritious food that has high economic value for the people of Harjomulyo Village. In solving the problem, it is carried out by extension methods and discussions about the benefits of moringa plants for health and fulfillment nutrition for family, technical counseling on the process of moringa sticks, packaging of moringa sticks, and business and marketing analysis of moringa sticks.